Effects of authentic leadership, employee resilience, job satisfaction, and innovative work behavior on employee work performance in transport and logistics of Thailand - Pitchaya Srimongkolkul; Jumpoth Boriraj; Jedsada Wongsansukcharoen (Cogent Business & Management, 2025)
Leadership has emerged as a crucial concept as organizations endeavor to maximize employee performance. Authentic leadership has attracted increasing attention because of its potential to positively influence employee outcomes. This study investigates the impact of authentic leadership on employee work performance in Thailand’s logistics sector. We aim to address research gaps by exploring potential mediators such as employee resilience, job satisfaction, and innovative work behavior. We use a sample of 614 logistics employees in the Eastern Economic Corridor of Thailand. We use quantitative and structural equation modeling. The findings demonstrate that authentic leadership exerts a direct influence on employee work performance, especially when moderated by employee resilience. Authentic leadership has a weaker correlation with innovative work behavior, even though innovative work behavior significantly affects employees’ work performance. Additionally, an unexpected finding reveals that higher work performance may be less related to lower job satisfaction, possibly because of stress or increased workload. The results suggest that leaders should embrace authentic leadership, foster employee resilience, and cultivate innovative work behavior. These factors contribute to a supportive work environment and improve employees’ long-term work performance.